Repercussão do pré e pós-condicionamento muscular esquelético com laser de baixa intensidade em marcadores bioquímicos de lesão e inflamação em ratas submetidas à uma sessão de exercício resistido - Oliveira, Helenita Antonia de (2016)
Experimental and clinical studies have demonstrated positive effects of low level laser therapy (LLLT) on the reduction of muscle damage markers and inflammatory profile, post exercise. Objective: To analyze the effect of the application of LLLT (830 nm) before and after the resistance exercise session, in biochemical markers of muscle injury and inflammation in rats. Methods: 99 Wistar rats were divided into five groups: Ctr (n = 12) - animals that received no energy; 2J, 4J and 8J (n = 12) - animals that received 2J, 4J and 8J of energy, prior to physical exercise; 4J-post (n = 8) -animals that received 4J of energy post-exercise. LLLT was applied to the gastrocnemius muscle bilaterally. Instantly post irradiation, the animals were submitted a single exercise session, which consisted of four climbs on the ladder carrying the maximum load. The 4J- post group received irradiation instantly post the exercise session. Blood was collected before, instantly and 24 hours after the resistance exercise session, for serum creatine kinase (CK), lactate dehydrogenase (LDH) and lactate. Then, the animals were euthanized and the right gastrocnemius muscle was collected for analysis of gene expression of IL-1β, IL-6, IL-10, TNF-α, MCP-1, CINC-1 inflammatory cytokines. Results: Previous application of LLLT attenuated blood lactate levels and enzymatic activity of CK and LDH, instantly post exercise, in the 4J group in relation to resting levels. Post 24h, these effects did not differ in CK levels, LDH remained high in all groups. In the gene expression, there was reduction in the 4J group at the concentration of IL-6 (p <0.05); IL-1β, CINC-1 and MCP-1 (p <0.001) instantly post exercise in relation to the control group. Post 24 h this effect was found on TNF-α, IL-6 (p <0.05) and MCP-1 (p <0.01). In the 4J post exercise the CK and LDH levels were lower only in the 24h analysis. Effect also found on cytokines IL-1β, CINC-1, IL-10 (p <0.0001) and MCP-1 (p <0.02), which had a reduction in relation to the control group. Conclusion: The results indicate that LLLT applied prior or post exercise was effective in reducing muscle injury markers and attenuating inflammation, and the best effects were achieved with 4 J irradiation.